Efektivitas produksi dan efisiensi biaya produksi nelayan tangkap pancing tonda ikan tuna di Desa Kondowa Kecamatan Pasarwajo Kabupaten Buton - Lela, Wa; La Ola, La Onu; Kamri, Syamsul (Jurnal Sosial Ekonomi Perikanan, 2021)
Differences in catch as well as the costs incurred in one fishing trip of troll fishermen has been known. Therefore, effective and efficient fishing cost are required to maximize fishermen revenue and thus income. The purpose of this study is to examine the efficacy and efficiency of production costs carried out by trolling fishermen in Kondowa Village, Pasarwajo District, Buton Regency. This research was conducted during the period of August to September 2020. Respondents in this study were the entire population of 13 tuna trolling fishermen in the village. Data were obtained through direct interviews using a questionnaire. Primary data collected included fuel costs, consumption, total catch per trip and sales price, whereas secondary data consisted of population, fishermen education level and other data related to this study. The data obtained were analyzed using the formula of total cost, revenue, production efficacy and production cost efficiency. The results of the analysis showed that the highest production was 82 kg with an efficacy level of 0.0000257, and the lowest efficacy was 0.0002902 with a production of 73 kg. The highest efficiency level of fishermen in one fishing trip was Rp.38. 955 / kg and the lowest was Rp3,446 / kg. The results of this study indicated that the production efficiency of trolling fishermenin Kondowa Villagewas very minimum but has not been effective that may due to the fishing rod used only one hook in each reel. Increasing the number of hook may increase the efficacy and subsequently the revenue of trolling fishermen.